2014
DOI: 10.1111/nph.12983
|View full text |Cite
|
Sign up to set email alerts
|

Variation in plant defences among populations of a range‐expanding plant: consequences for trophic interactions

Abstract: SummaryAlthough plant-herbivore-enemy interactions have been studied extensively in cross-continental plant invasions, little is known about intra-continental range expanders, despite their rapid spread globally.Using an ecological and metabolomics approach, we compared the insect performance of a generalist and specialist herbivore and a parasitoid, as well as plant defence traits, among native, exotic invasive and exotic non-invasive populations of the Turkish rocket, Bunias orientalis, a range-expanding spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…While many studies have examined the impact of generalist herbivory on plant resistance, they have produced inconsistent results. In some cases, invasive populations have higher resistance to generalists than native populations (Leger & Forister, ; Caño et al ., ; Liao et al ., ), while results from other studies have found the opposite pattern (Siemann & Rogers, ; Hull‐Sanders et al ., ; Fortuna et al ., ). Such observed differences may be caused by a species‐specific response, especially when only a few generalists are examined.…”
Section: Discussionmentioning
confidence: 97%
“…While many studies have examined the impact of generalist herbivory on plant resistance, they have produced inconsistent results. In some cases, invasive populations have higher resistance to generalists than native populations (Leger & Forister, ; Caño et al ., ; Liao et al ., ), while results from other studies have found the opposite pattern (Siemann & Rogers, ; Hull‐Sanders et al ., ; Fortuna et al ., ). Such observed differences may be caused by a species‐specific response, especially when only a few generalists are examined.…”
Section: Discussionmentioning
confidence: 97%
“…Although analysis of neutral markers suggests genetic drift has been particularly strong in Australia (van Boheemen et al, 2017), we did not reveal any increase in inducible variation. The growing body of literature testing constitutive versus inducible defence in native and introduced ranges frequently report inconsistent results varying from reductions, to maintenance, to increases in either defence (Agrawal et al, 2015;Beaton, Zandt, Esselman, & Knight, 2011;Carrillo, Wang, Ding, Klootwyk, & Siemann, 2012;Cipollini & Lieurance, 2012;Cipollini et al, 2005;Eigenbrode et al, 2008;Fortuna et al, 2014;Gu et al, 2014;Macel et al, 2017;Wang et al, 2013Wang et al, , 2012 and calls for more detailed research on the cost-benefit trade-offs of the various responses.…”
Section: Constitutive Versus Induced Range Divergencementioning
confidence: 99%
“…A subset of those species also possessed faster root turnover, which was associated with higher N uptake and faster growth capacity between native and exotic congeners (Smith, Fridley, Goebel, & Bauerle, 2014). Furthermore, selective herbivory on native and exotic species may additionally alter nutrient and energy transfer in invaded ecosystems (Cincotta, Adams, & Holzapfel, 2009;Fortuna et al, 2014).…”
Section: Species Pool Influences On Native and Exotic Traitsmentioning
confidence: 99%